Predicting Engagement in Older Adults With and Without Dementia While Playing Mobile Games (2021)
The number of older adults with dementia and related cognitive impairments continues to rise worldwide. Decline in certain cognitive skills, memory, and attention in this population is associated with deterioration in functioning in daily activities and a reduced quality of life. Engagement in cognitively stimulating activities can help prevent cognitive decline in older adults [1]. Research suggests that regularly playing mobile games could improve several cognitive functions that naturally deteriorate with age and even more with dementia. If mobile games are easy-to-use and engaging enough, they may be a valid intervention and assessment tool for cognitive functioning in older adults with cognitive impairment or dementia [2]–[4]. The level of engagement may influence the therapeutic effect of mobile game interventions [5]. Engagement is the degree of absorption, immersion, and involvement in a task. The theoretical foundation of engagement lies in Flow Theory [6]. Flow has been described as a subjective state that people report when they are completely involved in something to the point of forgetting time, fatigue, and everything else but the activity itself [6]. The literature shows that engagement is mainly recognized through analyzing participants’ bio-signals, principally in young people [7]–[8]. The development of methods to recognize engagement in older adults is needed. The aim of this study was to investigate the factors that influence engagement in older adults who play mobile games.